Exploring the recent trends in perturbing the cellular signaling pathways in cancer by natural products - Rahman, Md. Mominur; Sarker, Md. Taslim; Alam Tumpa, Mst. Afroza; Yamin, Md.; Islam, Tamanna; Park, Moon Nyeo; Islam, Md. Rezaul; Rauf, Abdur; Sharma, Rohit; Cavalu, Simona; Kim, Bonglee (Frontiers in Pharmacology, 2022)
Cancer is commonly thought to be the product of irregular cell division. According to the World Health Organization (WHO), cancer is the major cause of death globally. Nature offers an abundant supply of bioactive compounds with high therapeutic efficacy. Anticancer effects have been studied in a variety of phytochemicals found in nature. When Food and Drug Administration (FDA)-approved anticancer drugs are combined with natural compounds, the effectiveness improves. Several agents have already progressed to clinical trials based on these promising results of natural compounds against various cancer forms. Natural compounds prevent cancer cell proliferation, development, and metastasis by inducing cell cycle arrest, activating intrinsic and extrinsic apoptosis pathways, generating reactive oxygen species (ROS), and down-regulating activated signaling pathways. These natural chemicals are known to affect numerous important cellular signaling pathways, such as NF-B, MAPK, Wnt, Notch, Akt, p53, AR, ER, and many others, to cause cell death signals and induce apoptosis in pre-cancerous or cancer cells without harming normal cells. As a result, non-toxic "natural drugs" taken from nature's bounty could be effective for the prevention of tumor progression and/or therapy of human malignancies, either alone or in combination with conventional treatments. Natural compounds have also been shown in preclinical studies to improve the sensitivity of resistant cancers to currently available chemotherapy agents. To summarize, preclinical and clinical findings against cancer indicate that natural-sourced compounds have promising anticancer efficacy. The vital purpose of these studies is to target cellular signaling pathways in cancer by natural compounds.